Managing Efficiency of Urban Road Toward Better Transport System - Ripan Debnath; Mohammed Shariful Islam; Khan Rubayet Rahuman (Journal of Regional and City Planning, 2008)
Increased  trafiic  volume  introduces  congestion  on  road  affecting  efficiency  of  road.  Efiiciency assessment could be defined as the comparison between current status of roads in terms of road capacity, traflic volume, geometric design, etc. And standard of roads prescribed for well-functioning of roads. Afier the opening of Rupsha Bridge in Khulna of Bangladesh, the study road gains some additional trips : the trips previously used Rupsha Ferry terminal and trips from city center people make to visit the Bridge. The burden of traffics in an urban road result congestion on it and which makes necessity of studying  whether  the  road  is  efficient  or  not  to  serve  all  its  traflic  flow.  This  study  presents  a methodological approach toward measuring efficiency of an urban road and also depicts when and how such measure might be required for an urban setting. This study conducts traflic volume, geometric design status and problem analysis to identify the problems making traffic congestion. Datasets of the road,  comparing  with  the  road  standards,  prove  the  road  as  an  ineflicient road.  The  authors  also discovered what the vehicle types responsible for such inefficiency are. They suggested with appropriate reasoning that motorized vehicles required to be eliminated from the road to have efficiency serving the residential  trips  and  additional  visitor  trips  on  the  road.  The  authors  concluded  by  designing  an alternative road for the eliminated motorized vehicles.